Pengembangan Sistem Aplikasi Pencarian Dosen Pembimbing Skripsi dengan Teknologi Web Semantik (Studi Kasus : Fakultas Ilmu Komputer Universitas Brawijaya) - Eka Devi Prasetiya; Bayu Priyambadha; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The implementation of the thesis at the Faculty of Computer Science, University of Brawijaya (FILKOM UB) experienced several obstacles experienced by students. One of the obstacles is that it is difficult for students to choose prospective thesis supervisors who are suitable with the thesis topic to be examined. One way that can be done is to know the thesis that has been guided by a lecturer. Journal of Information Technology and Computer Science Development (JPTIIK) is a website that provides thesis information from FILKOM UB students. Students can search for theses that are guided by lecturers by searching based on keyword names of lecturers on JPTIIK. But the search results on JPTIIK are often irrelevant, because the data sought is not interconnected. In this study, a thesis supervisor application search system was developed that uses semantic web technology to connect and map data. Data is mapped into ontologies to facilitate searching. The search system is supported by cosine similarity so that search results can be ranked based on the degree of similarity of the thesis. The development method used in this system is the waterfall method. The system is tested using unit tests, validation and compatibility. The results of validation testing conducted in all test cases give a value of 100% valid.